Toward the 2026 Mandatory Halal Certification: MSME Compliance and a Responsive Law Enforcement Model in East Aceh Regency - Eka Syahputra; Muhammad Dayyan; Muzakkir Muzakkir; Faisal Alfaerah (International Journal of Sharia Studies, 2026)
This study examines the legal framework of Indonesia's mandatory halal certification policy ahead of the 2026 implementation deadline, identifies the factors influencing the compliance of micro, small, and medium enterprises (MSMEs), and formulates a responsive law enforcement model for East Aceh Regency. The research employs a normative legal method supported by limited empirical data, using statutory, conceptual, and case approaches to analyze relevant regulations, scholarly literature, and field information. The findings indicate that the post-2024 legal framework has strengthened legal certainty and expanded access to halal certification. However, MSME compliance continues to be influenced by legal literacy, administrative capacity, documentation, perceptions of cost and procedural complexity, and the uneven availability of assistance. The study proposes a responsive enforcement pyramid that emphasizes public outreach, assisted compliance, corrective warnings, proportionate administrative sanctions, and targeted enforcement against repeated violations. It contributes a responsive law enforcement model that balances legal certainty with MSME empowerment, thereby strengthening consumer protection and supporting the more effective implementation of Indonesia's mandatory halal certification policy.